Effect of Extracts from Zygophyllim fabago on Growth of Some Bacteria - Banno, I. S.; Al-Qasi, I. E.E. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The present study was carried out to evaluate antibacterial activity of water , alcoholic extracts (cold and hot) and the crude alkaloid extract of leaves, seeds and roots of Zygophyllum fabago plant against the growth of some bacteria including gram negative bacteria(Escherichia coli ,Pseudomonas aeruginosa) and gram positive bacteria(Staphylococcus aureus ,Bacillus subtilis). Results showed variation in antibacterial activity of different extracts against the studied bacteria. Hot alcoholic extracts showed the highest antibacterial activity followed by hot water extract. Additionally, alcoholic extracts of seeds revealed a higher activity compared with other plant extract.Results of sensitivity of bacteria towards crude extracts,showed the following: B.subtilis was more sensitive,its growth inhibited by all extracts of Z.fabago, with MIC (1040)mg/ml, followed by S.aureus MIC with (10-50)mg/ml, then E.coli was with MIC(1060)mg/ml, finally P.aeruginosa which was the most resistant for all exracts and MIC was with (20-70)mg/ml. Crude alkaloid extracts from different plant parts also differed in their activity against these bacteria, where the seeds alkaloid extract was the most effective, followed by the alkaloid extract of leaves and roots. Bioautography of seeds alkaloid extracts using TLC technique showed the presence of three compounds which differed in their Rf values, only one compound of these three showed antibacterial activity tested against B. subtilis.